THE RELATIONSHIP OF LEUKOARAIOSIS WITH CLINICAL OUTCOMES OF STROKE FUNCTIONAL AND COGNITIVE FUNCTION IN THROMBOSIS TYPE ISCHEMIC STROKE PATIENTS - Lailatul Fadhila (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Introduction: Leukoaraiosis is a white matter disorder of the brain that can be detected through head CT scan or MRI, associated with worse clinical outcomes. A greater volume of leukoaraiosis is associated with a higher National Institute of Health Stroke Scale (NIHSS). Objective: To determine the relationship of leukaraiosis toward functional clinical outcomes and cognitive function of patients with thrombosis type ischemic stroke. Method: Observational analytical research with cross sectional design. The study sample was taken based on consecutive sampling in patients with thrombosis type ischemic stroke treated at RSUD dr. Zainoel Abidin Banda Aceh from February 2024 to April 2024. Functional clinical outcomes assessed using NIHSS and cognitive function assessed using Montreal Cognitive Assessment (MoCa-Ina). Results: 75 samples that met the research criteria were obtained. The study was dominated by patients with leukoaraiosis (50.7%). The severity of leukoaraiosis was strongly associated with negative direction to functional outcomes (r = -0.602; p = 0.0001) and cognitive function (r = -0.726; p = 0.0001). The best cut off values for leukoaraiosis severity in predicting functional outcomes were grade 2 (sensitivity 56.5%; specificity 86.5%) and grade 1 for predicting cognitive function (sensitivity 73.1%; specificity 95.7%). Discussion: It was found that severity of leukoaraiosis is related to the clinical functional outcomes and cognitive function of patients with thrombosis type ischemic stroke with a strong and negative direction relationship. The severity of leukoaraiosis is a good predictor of the patient's clinical functional outcomes and cognitive function. Keywords: Cognitive Function, Ischemic Stroke, Leukoaraiosis, MoCa-Ina, NIHSS